How Well Can We Target Resources with Quick-and-Dirty Data?: Empirical Results from Cambodia - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2006)
Proverty reduction is a top priority for international organizations, governments and non-gorvernmental organizations. The aid resources available for poverty reduction are, however, severely constrained in many countries. Minimizing the leakage of aid resources to the non-poor is a key to maximize poverty reduction with the limited amount of resources available. One Way to minimize such leakage to to target resources geographically. That is, policmakers can move resources to the poorest parts of the country. Geographic taregting can quite effective when poverty is unevenly distributed across the country, and this proves to be the case in many countries.